HUBUNGAN ASUPAN PROTEIN, ZAT BESI, VITAMIN C, FITAT, DAN TANIN TERHADAP KADAR HEMOGLOBIN CALON PENDONOR DARAH LAKI-LAKI (Studi di Unit Donor Darah PMI Kota Semarang) - Setyaningsih, Rini Indah; Pangestuti, Dina Rahayuning; Rahfiludin, M . Zen (Fakultas Kesehatan Masyarakat, 2018)
In 2017, 95.26% of 21,098 blood donor candidates was failed to donate their blood because the hemoglobin level did not meet the requirement. Nutritional status is one of the factors that influences hemoglobin level. The aim of this research is to analyze the relationship of protein, iron, vitamin C, phytate, and tannin intake towards the hemoglobin level. The research method used was explanatory research with cross-sectional design. The sampling technique used was purposive sampling with samples as many as 46 subjects of male blood donors in Blood Donor Unit of Indonesian Red Cross in Semarang City. The data were collected through interview method with structured questionnaire and the data of nutrition intake were collected with semiquantitative FFQ. The normality test used Shapiro-wilk. Data analysis used correlation test and Chi-Square test. The results showed average BMI of the respondents 26.6±4.57 kg/m2 and hemoglobin level of 15.2±1.48 g/dL. The results also showed the average of protein sufficiency of the respondents 44,4±22,25%, 78,4±32,71% of iron, 20,6±6,94% of vitamin C, 1056,7±227,89 mg of phytate intake, 2±1,6 mg of tannin intake. There was a relationship between the total of sufficiency level of protein (r=0,466 p=0,000), iron (r=0,423 p=0,003), vitamin C (r=0,352 p=0,017), and intake of tannin (r=-0.555 p=0,000) towards hemoglobin level. There was no relation between the intake of phytate (r=0,008 p=0,957) towards hemoglobin level. The conclusion, the sufficiency level of protein, iron, vitamin C and the amount of tannin intake related with the hemoglobin level.